Analisis Metode Pattern Based Approach Question Answering System Pada Dataset Hukum Islam Berbasis Bahasa Indonesia - Ade Iriani Sapitri; Said Al-Faraby; Adiwijaya Adiwijaya (STMIK Budi Darma, 2018)
Islamic law is a provision of the command of Allah SWT which has different laws. It takes a long time in the process of searching information manually given the many types of islamic law. From the above problems with the help of Question Answering System can solve the problem. The purpose of this study is to assist usesrs in finding the required information with input in the form of question with property category (OBJECT) What, (PERSON) Who, (LOCATION) Where, (TIME) When and (COUNT) How much. Research Question Answering System is implemented with the Pattern Based Approach method based on pattern classification. In this research we get the result of accuracy of answer equal 64,5% in every type of question category “What”,”When”,”How much”, “Who”, and “Where” with answer accuracy equal to 63,3%, 65%, 73,3%, 65% and 40%. From the accuracy results obtained that the method of Pattern Based Approach is able to be implemented in Question Answering System to solve the above problems